SEMA4D compromises blood–brain barrier, activates microglia, and inhibits remyelination in neurodegenerative disease - Ernest S. Smith (Neurobiology of Disease, 2015)
Multiple sclerosis (MS) is a chronic neuroinflammatory disease characterized by immune cell infiltration of CNS, blood–brain barrier (BBB) breakdown, localized myelin destruction, and progressive neuronal degeneration. There exists a significant need to identify novel therapeutic targets and strategies that effectively and safely disrupt and even reverse disease pathophysiology. Signaling cascades initiated by semaphorin 4D (SEMA4D) induce glial activation, neuronal process collapse, inhibit migration and differentiation of oligodendrocyte precursor cells (OPCs), and disrupt endothelial tight junctions forming the BBB. To target SEMA4D, we generated a monoclonal antibody that recognizes mouse, rat, monkey and human SEMA4D with high affinity and blocks interaction between SEMA4D and its cognate receptors. In vitro, anti-SEMA4D reverses the inhibitory effects of recombinant SEMA4D on OPC survival and differentiation. In vivo, anti-SEMA4D significantly attenuates experimental autoimmune encephalomyelitis in multiple rodent models by preserving BBB integrity and axonal myelination and can be shown to promote migration of OPC to the site of lesions and improve myelin status following chemically-induced demyelination. Our study underscores SEMA4D as a key factor in CNS disease and supports the further development of antibody-based inhibition of SEMA4D as a novel therapeutic strategy for MS and other neurologic diseases with evidence of demyelination and/or compromise to the neurovascular unit.